Evaluasi Kinerja Balai Kemasan Produk Daerah Provinsi Nusa Tenggara Barat Berbasis ISO 9001:2015 - Heldy Sardianto; Kiki Yulianto; Khotibul Umam (Performa: Media Ilmiah Teknik Industri, 2022)
Balai Kemasan Produk Daerah (BKPD) has implemented ISO 9001: 2015 since 2019 and received the certificate in 2020. This study aims to determine the extent to which the ISO 9001:2015 standard has been implemented at Balai Kemasan Produk Daerah  in order to improve service to consumers. The method used is a descriptive qualitative method using a gap analysis technique, which is to calculate the gap between the 10 clauses contained in ISO 9001: 2015 and the reality at Balai Kemasan. Collecting data is assisted by a checklist compiled based on 10 clauses in ISO 9001: 2015 and adapted to the quality guidelines of Balai Kemasan. Based on the results of the analysis using gap analysis, it was found that the implementation of ISO 9001: 2015 in Balai Kemasan was only 57.35%. So it can be concluded that the implementation is not as expected, improvements must be made to improve the performance of Balai Kemasan.